The impact of quantitative easing on liquidity creation - Kapoor, Supriya; Oana, Peia (My University, 2021)
We study the effects of the US Federal Reserve’s large-scale asset purchase programs during 2008–2014 on bank liquidity creation. Banks create liquidity when they transform the liquid reserves resulted from quantitative easing (QE) into illiquid assets. As the composition of banks’ loan portfolio affects the amount of liquidity it creates, the impact of quantitative easing on liquidity creation is not a priori clear. Using a difference-in-difference identification strategy, we find that banks more affected by the policy increased lending relative to those less affected, mainly during the first and third round of QE. However, we only find a strong effect of the policy on liquidity creation during the third round of QE. This points to a weaker impact on the real economy during the first two rounds, when more exposed banks transformed the reserves created through QE into less illiquid assets, such as real estate mortgages.
Keywords: Large-scale asset purchases; Quantitative easing; Liquidity creation; Bank lending; Banking; CENTRAL BANKS; LIQUIDITY; QUANTITATIVE EASING; bank lending; impact of financial crisis; Policy